Analisis Tataran, Platform, dan Fitur E-CRM: Sebuah Tinjauan Literatur Sistematis - Wijaya, Hendri; Setiawan, Fery; Dillon, Erloy; Farisi, Ahmad (MDP Student Conference, 2025)
Electronic Customer Relationship Management (E-CRM) is a strategic solution used by organizations to enhance customer relationships through digital technology. This study aims to answer four key questions in E-CRM development, namely: the levels of CRM applied, the platforms supporting implementation, the main features developed, and the objectives of E-CRM development. The research method used is a Systematic Literature Review (SLR), which includes data collection from leading academic databases, filtering using inclusion and exclusion criteria, and thematic analysis of relevant literature. The results show that E-CRM development involves strategic, operational, and analytical levels. The platforms used include cloud, hybrid, and on-premise solutions, selected based on organizational needs. The identified key features are marketing automation, customer data management, personalized interactions, and artificial intelligence-based analytics. Additionally, the primary goals of E-CRM development include improving customer loyalty, operational efficiency, and more accurate data-driven decision-making. This study provides valuable insights into E-CRM implementation and offers practical guidance for organizations to address the challenges of managing customer relationships in the digital era.